Palembang-Malay Women's Resistance against the Domination of Patriarchal Culture in the XX Century - Rochmiatun, Endang (Diponegoro University, 2023)
Gender issues during the early twentieth century in Palembang were worth nothing. Among the reasons were that during the colonial period, women did not have equal opportunities to contribute to the public sphere as men. This proves that women's access to public activities is limited. This research manifests women's struggle for emancipation against patriarchal culture in the public sphere in the city of Palembang. This research uses historical research methods and qualitative research. It seeks to answer three questions; 1) How did the Palembang women carry out the emancipation movement against the domination of patriarchal culture? 2) What forms of movement did Palembang women take? 3) What public sectors could Palembang’s women be achieved in the twentieth century. Until the beginning of the 20th century, the traditions and understanding of the people in Palembang did not realize the importance of women obtaining formal education. Not many parents want to send their daughters to formal schools. Whereas in Palembang there were already formal schools in the early 20th century, including: Madrasah al-Islamiyah, HIS School, Muhammadiyah School. Many parents who have daughters still view formal education as unimportant, women are only obliged to be in the domestic sphere (become a wife, do household chores). This condition is the reason why some women who have realized the importance of women getting formal education then voiced the public's awareness of the importance of women getting the right to go to school. Several forms of women's struggle so that the tradition in Palembang that views formal education as not important for women can change, including: Writing in a newspaper published in Palembang. This research shows the struggle of Palembang women in voicing their rights in the public sphere in the twentieth century through the mass media despite many obstacles. The evidence of women's struggle for emancipation gradually eliminates the patriarchal culture.